Public industrial areas of Ukraine in the condition of social catastrophe in 1917-1920 - Viacheslav Popov (Cхід, 2013)
In this article on archival sources, deals with the activity of individual members of the public industrial areas of Ukraine in 1917-1920. to ensure that vital material goods. The factors impeding such activity, formulated two main types of behavior in extreme circumstances, attempt to analyze the social composition of the population depending on the model behavior.